Nutritional status evaluation and nutrient intake in adult patients with pulmonary tuberculosis and their contacts - Eduardo Campos-Gongora; Julieta López-Martínez; Joselina Huerta-Oros; Gerardo I Arredondo-Mendoza; Zacarías Jiménez-Salas (Journal of Infection in Developing Countries)
Introduction: Malnutrition is a common status in patients with tuberculosis (TB). Because TB is disseminated through the sputum of infected persons, individuals who maintain relations with a TB patient are at high risk of infection; this risk is greater when contacts present an inadequate nutritional status. The aim of this work was to analyse and compare the nutritional status and macro and micronutrient intake of TB patients and their household contacts.